THE IMPACT OF TOLL ROAD CONSTRUCTION ON CHANGES IN BUILT-UP LAND (CASE STUDY OF TRANS JAVA TOLL ROAD) - Fakhruddin, Ahmad; Gultom, Yohanna M.L. (UI Scholars Hub, 2021)
This study aims to see the impact of toll road construction of the Trans Java toll road on changes in a built-up land. The data processing and analysis in this study uses a difference-in-difference approach to see the impact before and after the construction of the toll road. This study uses district/city administrative boundaries as the unit of analysis and 92 regencies or cities. The selection of locations that are the focus of the research is based on the regency/cities through which the toll road passes as well as those bordering the regency/cities through which the toll roads pass.. The results of data processing and analysis show that there is an increase in the area of built-up land by 7% when compared to regency/cities that are not passed by toll roads. From a policy perspective, the construction of the Trans Java toll road can be said to have a positive impact on the built up land. That is, the closer to access, the more economic activity and growth of built up land